Whiter : Asian American women on skin color and colorism - Khanna, Nikki, 1974- (New York University Press, 2020)
Heartfelt personal accounts from Asian American women on their experiences with skin color bias, from being labeled "too dark" to becoming empowered to challenge beauty standards "I have a vivid memory of standing in my grandmother's kitchen, where, by the table, she closely watched me as I played. When I finally looked up to ask why she was staring, her expression changed from that of intent observer to one of guilt and shame. ... 'My anak (dear child), ' she began, 'you are so beautiful. It is a shame that you are so dark. No Filipino man will ever want to marry you.'"--"Shade of Brown," Noelle Marie Falcis How does skin color impact the lives of Asian American women? In Whiter, thirty Asian American women provide first-hand accounts of their experiences with colorism in this collection of powerful, accessible, and brutally honest essays, edited by Nikki Khanna. Featuring contributors of many ages, nationalities, and professions, this compelling collection covers a wide range of topics, including light-skin privilege, aspirational whiteness, and anti-blackness. From skin-whitening creams to cosmetic surgery, Whiter amplifies the diverse voices of Asian American women who continue to bravely challenge the power of skin color in their own lives